Altered Cell Wall Plasticity Can Restrict Plant Growth under Ammonium Nutrition - Podgórska, Anna; Burian, Maria; Gieczewska, Katarzyna; Ostaszewska-Bugajska, Monika; Zebrowski, Jacek; Solecka, Danuta; Szal, Bożena (Frontiers in Plant Science, 2017)
Plants mainly utilize inorganic forms of nitrogen (N), such as nitrate (NO3-) and ammonium (NH4⁺). However, the composition of the N source is important, because excess of NH4⁺ promotes morphological disorders. Plants cultured on NH4⁺ as the sole N source exhibit serious growth inhibition, commonly referred to as “ammonium toxicity syndrome.” NH4⁺-mediated suppression of growth may be attributable to both repression of cell elongation and reduction of cell division. The precondition for cell enlargement is the expansion of the cell wall, which requires the loosening of the cell wall polymers. Therefore, to understand how NH4⁺ nutrition may trigger growth retardation in plants, properties of their cell walls were analyzed. We found that Arabidopsis thaliana using NH4⁺ as the sole N source has smaller cells with relatively thicker cell walls. Moreover, cellulose, which is the main load-bearing polysaccharide revealed a denser assembly of microfibrils. Consequently, the leaf blade tissue showed elevated tensile strength, indicating higher cell wall stiffness. These changes might be related to changes in polysaccharide and ion content of cell walls. Further, NH4⁺ toxicity was associated with altered activities of cell wall modifying proteins. The lower activity and/or expression of pectin hydrolyzing enzymes and expansins might limit cell wall expansion. Additionally, the higher activity of cell wall peroxidases can lead to higher cross-linking of cell wall polymers. Overall, the NH4+-mediated inhibition of growth is related to a more rigid cell wall structure, which limits expansion of cells. The changes in cell wall composition were also indicated by decreased expression of Feronia, a receptor-like kinase involved in the control of cell wall extension.